Crop-weed competition in aerobic rice (Oryza sativa) — serious concern in nitrogen fertilizer management - GHOSH, AMAL; ANKIT; SINGH, R K; SINGH, O N (The Indian Journal of Agricultural Sciences, 2021)
Aerobic rice (Oryza sativa L.) is a climate resilient agro-technology thriving over the threats of looming water scarcity. However, severe crop-weed competition is the crux of the problem affecting N use efficiency that could result in drastic grain yield reduction. Thus, what would be the efficient weed management minimizing crop-weed competition for higher grain yield was studied at farmer’s fields under ICAR-NRRI, Cuttack and GBPUAT, Pantnagar during 2015-16 and 2016-17. Results showed that maintaining crop-weed competition during initial 75, 60 and 45 days crop growth accelerated N uptakes at 106.0 to 106.6 kg/ha, 105.5 to 105.8 kg/ha and 100.0 to 101.2 kg/ha enhancing grain yield by 5.25 to 5.56 t/ha, 5.0 to 5.4t/ha and 4.7 to 5.15 t/ha respectively. Corresponding weedy crop stands produced 0.90 to 1.35 t/ha, 1.10 to 1.48 t/ha and 2.45 to 2.86 t/ha grain yields only. Thus, average N gain of 0.22 and 0.17% were attributed to initial 75 and 60 days weed-free stands over initial soil N. While, N losses were maximum of 25.36, 24.56 and 22.32% at initial 60 and 75 days weedy stands and initial 15 days weed free stands respectively. Minimum N losses of 1.26 and 1.63% were at initial 15 days weedy crop or initial 45 days weed-free stands respectively. Therefore, on-farm validation at farmer’s fields could imply significance of declining crop-weed competition preferably up to initial 30-45 days promoting N use efficiency for higher aerobic rice production.